Relations between fatigue strength and other mechanical properties of metallic materials. (3rd April 2014) - Pang, J. C.; Li, S. X.; Wang, Z. G.; Zhang, Z. F.
ABSTRACT The relations between fatigue strength and other mechanical properties especially the tensile strength of metallic materials are reviewed. After analyzing the numerous fatigue data available, the qualitative or quantitative relations between fatigue strength and hardness, strength (tensile strength and yield strength) and toughness (static toughness and impact toughness) are established. Among these relations, the general relation between fatigue strength σw and tensile strength σb, σw = σb(C − P ⋅ σb), where C and P are parameters, (hereafter, the general fatigue formula) can well predict the fatigue strength with increasing the tensile strength in a wide range for many materials such as conventional metallic materials, newly developed materials and engineering components. On the basis of the experimental results of many materials, the fatigue damage mechanism, especially for high‐strength steels, is proposed. It is suggested that the general fatigue formula can provide a new clue to predict the fatigue strength and design the materials by adjusting material parameters P and C adequately.